Mediation Effects of Internal Financial Decisions and Company Performance on the Relationship of Macroeconomic Factors and Market Reactions - Indarto Indarto; Djoko Santoso (Soegijapranata Catholic University, 2021)
This study examines the effect of macroeconomic factors on investor reactions in the capital market with internal financial decisions and company performance as the intervening variables. Previous studies examined only the effect of macroeconomic factors on direct market reactions. The sample of this research are manufacturing companies listed on the Indonesia Stock Exchange. Structural Equation Modeling (SEM) was tested using SmartPLS. This study concludes that financial decisions and company performance are not the intervening variables between macroeconomic factors and market reactions. Macroeconomic factors do not affect the company's internal financial decisions and company performance but the market reaction. Meanwhile, the company's internal financial decisions have no effect on the company's performance and market reaction. The company's performance affects the market reaction. The results of this study prove that investors are very concerned about macroeconomic factors in making investment decisions. The dynamics of macroeconomic factors directly influence investment decisions in the capital market.